A Study of Non-Cognitive Factors Influencing Second Language Acquisition Of Elementary School Students Of Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research aimed to explore the non-cognitive factors influencing second language acquisition (SLA), with a particular focus on intrinsic motivation, anxiety, social interaction, and environmental influences. Through the analysis of survey data, the study highlights the profound impact these non-cognitive variables have on students’ ability to acquire a second language effectively.It also helps the teachers to improve the performance of learners by using non-cognitive strategies in their teaching learning process. Teachers will implement these non-cognitive strategies and improve the performance of learners by language acquisition.